Effect of type of diet on blood and plasma taurine concentrations, cardiac biomarkers, and echocardiograms in 4 dog breeds. (27th February 2021) - Adin, Darcy; Freeman, Lisa; Stepien, Rebecca; Rush, John E.; Tjostheim, Sonja; Kellihan, Heidi; Aherne, Michael; Vereb, Michelle; Goldberg, Robert
Abstract: Background: Associations of diet with dilated cardiomyopathy are under investigation. Objectives: That cardiac assessment would show abnormalities in healthy dogs eating grain‐free (GF) diets or diets with Food and Drug Administration (FDA)‐listed ingredients of concern (peas, lentils, or potatoes) as top 10 ingredients (FDA‐PLP), but not in dogs eating grain‐inclusive (GI) diets or diets without FDA‐listed ingredients of concern (PLP) in the top 10 ingredients (NoFDA‐PLP). Animals: One hundred eighty‐eight healthy Doberman Pinschers, Golden Retrievers, Miniature Schnauzers, and Whippets. Methods: This study was an observational cross‐sectional study. Echocardiograms, cardiac biomarkers, and blood and plasma taurine concentrations were compared between dogs eating GF (n = 26) and GI (n = 162) diets, and between FDA‐PLP (n = 39) and NoFDA‐PLP (n = 149) diets, controlling for age and breed. Demographic characteristics, murmurs, genetic status, and ventricular premature complexes (VPCs) during examination were compared between dogs eating different diet types. Results: No differences in echocardiographic variables, N‐terminal pro‐B‐type natriuretic peptide or whole blood taurine were noted between dogs eating different diet types. Dogs eating GF diets had higher median high‐sensitivity cardiac troponin I (hs‐cTnI) (GF 0.076 ng/mL [Interquartile range (IQR), 0.028‐0.156] vs. GI 0.048 [IQR, 0.0026‐0.080]; P < .001) and higher median plasma taurine (GF 125 nmol/mL [IQR, 101‐148] vs GI 104 [IQR, 86‐123]; P = .02) than dogs eating GI diets. Dogs eating FDA‐PLP diets had higher median hs‐cTnI (0.059 ng/mL [IQR, 0.028‐0.122]) than dogs eating NoFDA‐PLP diets (0.048 [IQR, 0.025‐0.085]; P = .006). A greater proportion of dogs eating FDA‐PLP diets (10%) had VPCs than dogs eating NoFDA‐PLP diets (2%; P = .04 ) . Conclusions and Clinical Importance: Higher hs‐cTnI in healthy dogs eating GF and FDA‐PLP diets might indicate low‐level cardiomyocyte injury.